2020
DOI: 10.1161/atvbaha.120.315261
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Factors From Proinflammatory Macrophages Promote an Osteoblast-Like Phenotype in Valvular Interstitial Cells

Abstract: Objective: Resident valvular interstitial cells (VICs) activate to myofibroblasts during aortic valve stenosis progression, which further promotes fibrosis or even differentiate into osteoblast-like cells that can lead to calcification of valve tissue. Inflammation is a hallmark of aortic valve stenosis, so we aimed to determine proinflammatory cytokines secreted from M1 macrophages that give rise to a transient VIC phenotype that leads to calcification of valve tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 53 publications
0
60
1
Order By: Relevance
“…The expression level of IL-6 was increased in calcified human aortic valves (Li et al, 2017b). Recombinant IL-6 can increase the expression of RUNX2 and osteopontin to promote the osteogenic differentiation of VICs; when IL-6 was inhibited by siRNA, the osteogenic differentiation of VICs was blocked in vitro (El Husseini et al, 2014;Grim et al, 2020). However, there is still no evidence for the function of miR-149-5p in osteogenic differentiation of VICs and CAVD and it could be explored in a future study.…”
Section: Discussionmentioning
confidence: 98%
“…The expression level of IL-6 was increased in calcified human aortic valves (Li et al, 2017b). Recombinant IL-6 can increase the expression of RUNX2 and osteopontin to promote the osteogenic differentiation of VICs; when IL-6 was inhibited by siRNA, the osteogenic differentiation of VICs was blocked in vitro (El Husseini et al, 2014;Grim et al, 2020). However, there is still no evidence for the function of miR-149-5p in osteogenic differentiation of VICs and CAVD and it could be explored in a future study.…”
Section: Discussionmentioning
confidence: 98%
“…Our data suggest a potential interplay between inflammatory cytokines and oscillatory flow on monocyte adhesion that may be relevant to CAVD. In fact, infiltrated monocyte-derived cells, such as macrophages, are enriched in calcified valves and show increased inflammatory and osteogenic activity [ 34 , 49 , 50 ]. Moreover, the enrichment of polarized macrophages in bicuspid valves and the activation of macrophages by cyclic mechanical strain in several models suggest a potential role for mechanical strain in macrophage activation and the ensuing inflammation in CAVD [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preventing valve fibrosis during AVS is crucial for long-term patient outcomes even after valve replacement interventions. Although previous studies have shown that alterations in serum protein levels after valve replacement can deactivate myofibroblasts 12,13 , the underlying mechanisms of this deactivation remain unclear due in part to the complexities of intracellular regulatory mechanisms. Using coupled serum proteomic and myofibroblast transcriptomic datasets for patients undergoing TAVR, we developed a strategy to integrate this patient-specific data into a computational model of myofibroblast signaling and transcriptional regulation to predict fibrosis-related protein expression in response to environmental signals.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar finding, Hilfiker-Kleiner and colleagues found decreases in ERK and Akt phosphorylation for mice carrying a point mutation in gp130 and subjected to MI compared to wild-type mice. Recent evidence of IL6 as a promoter of VIC osteogenic differentiation via the increased expression of RUNX2 and osteopontin suggest that this pathway may serve multiple phenotypic roles 13 , and future targeted investigations of this behavior may explain possible context-dependent roles of IL6 signaling during AVS progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation